Organic pollutant degradation via novel ZnCo2O4-embedded grafted waste polystyrene foam as heterogeneous catalysts for PMS activation - Asmaa A. Roshdy; Elsayed A. Elsharaky; Ahmed H. Elged; Abdelrahman M. Rabie (Applied Water Science)
Abstract This study aimed to design and fabricate high-performance heterogeneous polymeric composites via in-situ polymerization, utilizing waste polystyrene-co-methacrylic acid functionalized with zinc cobalt oxide (ZC) at varying loadings (10, 15 and 30 wt %), designated as m-WZC10, m-WZC15 and m-WZC30 respectively. Additionally, waste polystyrene (W) underwent methacrylic acid grafting in the absence of zinc cobalt oxide, serving as a control reference material, denoted as m-W, to evaluate the impact of ZC incorporation on the composite’s structural and catalytic properties. The synthesized polymers were employed for poroxymonosulfate activation (PMS) in the catalytic removal of methylene blue (MB) from wastewater streams. Through systematic experimentation, we compared three different loadings of m-WZC composites (m-WZC10, m-WZC15, and m-WZC30) by optimizing key degradation parameters, including PMS dose, pH, temperature, initial MB concentration, and the effect of ions. Among them, m-WZC15 exhibited the optimal performance, achieving 99.89% MB removal within just 10 min at an initial MB concentration of 20 mg/L. Under the optimal conditions of m-WZC15, the study further expanded its scope by investigating its efficacy in degrading other pollutants, methyl red (MR), methyl orange (MO), rhodamine B (RB), and p-nitrophenol (PNP). The catalysis exhibited excellent degradation activity, achieving removal rates of 99.76%, 99.0%, 98.3%, and 97.8% for these pollutants, respectively. Stability experiments revealed that the MB degradation rate achieved by the m-WZC15 remained consistently high, reaching 97% even after 5 cycles. Furthermore, no noticeable changes were observed in the crystalline phase structure throughout the experimental cycles. The synthesized m-WZC15 under these established conditions, demonstrated remarkable versatility and emerged as a promising candidate for water purification endeavors.